Surat Kabar sebagai Media Kritik Sosial di Indonesia 1966-1974 - Rubeno, Iksan; Shokheh, Mukhamad (Universitas Negeri Semarang, 2025)
In 1966, Suharto replaced Sukarno as the second President of the Republic of Indonesia. During his leadership, newspapers that had previously been banned under Sukarno’s administration were allowed to resume publication. This study aims to describe the role of newspapers as a medium of social criticism during the early phase of the New Order’s political consolidation, leading up to the events of January 15, 1974. The research employs a historical method. It explores the transition from Guided Democracy to the New Order, the process of the regime’s consolidation, the role of newspapers as a channel of social criticism between 1966 and 1974, and the New Order government's responses to criticisms raised by various press institutions. The study finds that although newspapers had some space to express criticism of the government during that period, the New Order regime imposed increasingly strict control over the press as authoritarianism strengthened.